2007
DOI: 10.1007/s10439-007-9394-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Human Teeth-Derived Hydroxyapatite

Abstract: We have been interested in human teeth which consist of hydroxyapatite (HA), but do not degrade for a long time. In order to overcome dissolution and mechanical degradation of man-made HA, biologically derived hydroxyapatite (BHA) ceramics were prepared from human teeth and their dissolving behavior was investigated in distilled water for 3-14 days and compared with an artificial HA made of synthetic HA powder. BHA ceramics were prepared by calcining freshly extracted human teeth at 900 degrees C and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
9
1
1
Order By: Relevance
“…These results indicate that more extensive calcification of new bone occurred in the BHA group compared with the AHA group. Seo and Lee reported that BHA could be a good candidate in biomedical applications to improve the microstructural and mechanical stability of HA ceramics [17]. In the present study we were unable to determine whether the multinucleated cells were osteoclasts, and no sign of HA degradation was observed, since the particle phagocytosis through macrophages was likewise not observed.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…These results indicate that more extensive calcification of new bone occurred in the BHA group compared with the AHA group. Seo and Lee reported that BHA could be a good candidate in biomedical applications to improve the microstructural and mechanical stability of HA ceramics [17]. In the present study we were unable to determine whether the multinucleated cells were osteoclasts, and no sign of HA degradation was observed, since the particle phagocytosis through macrophages was likewise not observed.…”
Section: Discussioncontrasting
confidence: 65%
“…In general, physical and chemical properties of HA materials are important factors affecting the dissolution process [13][14][15][16]. Seo and Lee investigated the comparison of dissolving behavior between BHA and AHA [17]. BHA showed rather stable grain boundaries and lack of excessive dissolution in a liquid environment.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the amount of ionic substitution in human teeth-derived hydroxyapatite was below the detection limits for XRD and FTIR measurements 33) . Therefore, a bigger suite of characterization techniques was employed in this study as there was a concern that marginal ion substitution into HA might not be detectable.…”
Section: Synthesis Of Fluorinated Phamentioning
confidence: 90%
“…Biological hard tissues such as bones [11, 14, 16, 37, 57] and teeth [58] are the main raw materials in the preparation of biological apatite. For the commercial bone grafting products, most of the bone-derived substitutes are from bovine bone.…”
Section: Preparation Of Biological Apatitementioning
confidence: 99%